2015
DOI: 10.1177/2047487315603186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chios mastic gum on cholesterol and glucose levels of healthy volunteers: A prospective, randomized, placebo-controlled, pilot study (CHIOS-MASTIHA)

Abstract: CMG has a significant lowering effect on total cholesterol and glucose levels of healthy volunteers, with excellent tolerance and no detectable side effects, especially in overweight and obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
(47 reference statements)
2
26
0
6
Order By: Relevance
“…There are preclinical and clinical data supporting its safe administration in IBD (Gioxari et al, ; Kaliora et al, , b), but this is the first study, according to our knowledge, evaluating the effectiveness of Mastiha on the basis of a phase‐II randomised placebo‐controlled clinical trial of both CD and UC patients in relapse. It is important to mention that no adverse effects were reported strengthening the safety profile of this natural product and coming into agreement with the results of other clinical studies that evaluated the effectiveness of mastiha in duodenal ulcer, dyspepsia, and hypercholesterolaemia with no adverse effects and excellent tolerability (Al‐Habbal, Al‐Habbal, & Huwez, ; Dabos et al, ; Kartalis et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…There are preclinical and clinical data supporting its safe administration in IBD (Gioxari et al, ; Kaliora et al, , b), but this is the first study, according to our knowledge, evaluating the effectiveness of Mastiha on the basis of a phase‐II randomised placebo‐controlled clinical trial of both CD and UC patients in relapse. It is important to mention that no adverse effects were reported strengthening the safety profile of this natural product and coming into agreement with the results of other clinical studies that evaluated the effectiveness of mastiha in duodenal ulcer, dyspepsia, and hypercholesterolaemia with no adverse effects and excellent tolerability (Al‐Habbal, Al‐Habbal, & Huwez, ; Dabos et al, ; Kartalis et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…Other study showed that Nigella sativa reduced fasting blood sugar (40). A randomized, placebo-controlled study showed that Chios mastic gum (CMG) has a significant lowering effect on total cholesterol and glucose levels of healthy volunteers (19). Although various studies have shown that the components of MDB are effective in weight loss, there is little evidence that a natural compound with a mechanism of action, results in successful treatment of obesity (41).…”
Section: Discussionmentioning
confidence: 99%
“…The ingredients of this product which are based on the books of Makhzan-al-Advia and Al-Qanun fi al-Tibb (from the important sources of Persian Medicine) have hot and dry temperament that is effective in the treatment of phlegmatic diseases including obesity (9,11). In various studies, anti-inflammatory and anti-oxidative effects (12)(13)(14)(15)(16) and lipid profile reducing effects (14,(17)(18)(19) of components of this herbal formulation have been proven. Considering the major role of oxidative stress in the pathophysiology of obesity, and the inverse relationship between indicators of antioxidant defense and body fat percentage and central obesity (20), MDB can be effective in the treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…the placebo compared to the verum group. Previous research showed that Mastiha lowers total cholesterol (Kartalis et al, 2016), which could be beneficial for IBD patients characterized by dyslipidemia and altered lipoprotein profile (Sappati Biyyani et al, 2010) While our study has interesting results and the quality of being fully double-blinded, it has limitations, including absence of colonoscopy at follow-up, precluding our ability to comment on histological alterations and the absence of the full metabolic profile identification. The study was however very tightly controlled to ensure compliance with the protocol, and had a final power of 0.90 for the between-subjects main effect at an effect size of 0.37.…”
Section: Accepted Manuscriptmentioning
confidence: 92%